Research on competencies of logistics specialists in transport organisations - Katinienė, Aušra; Jezerskė, Živilė; Vaičiūtė, Kristina (Journal of Business Economics and Management, 2021)
Successful activities of logistics specialists in transport organisations depend on their ability to adapt to a rapidly changing environment where the most changing and essential element – knowledge – is the most important constituent of competence. The lack of competencies of logistics specialists employed in transport organisations and the inconsistencies with the timely use of such competencies decrease the efficiency of performed functions and slow down organizational processes. As the result, employers are forced to deal with an alternative problem, i.e. whether to invest in inexperienced young logistics specialists for them to acquire competencies or to replace them with more experienced specialists. The article analyses the peculiarities of the competencies of logistics specialists and their use as a tool to ensure the development of logistics organisations and the quality of logistics services. The carried out qualitative research enabled the identification of the competence problems of logistics specialists – logistics manager and logistics forwarder – in transport organisations.